The Complex Interplay of Inflammation, Metabolism, Epigenetics, and Sex in Calcific Disease of the Aortic Valve - Ferrari, Silvia; Pesce, Maurizio (Frontiers in Cardiovascular Medicine, 2022)
Calcification of the aortic valve is one of the most rapidly increasing pathologies in the aging population worldwide. Traditionally associated to cardiovascular risk conditions, this pathology is still relatively unaddressed on a molecular/cellular standpoint and there are no available treatments to retard its progression unless valve substitution. In this review, we will describe some of the most involved inflammatory players, the metabolic changes that may be responsible of epigenetic modifications and the gender-related differences in the onset of the disease. A better understanding of these aspects and their integration into a unique pathophysiology context is relevant to improve current therapies and patients management.